Saintly Spheres and Islamic Landscapes : Emplacements of Spiritual Power across Time and Place - Ephrat, Daphna; Pinto, David G.; Wolper, Ethel Sara (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2021)
"Saintly Spheres and Islamic Landscapes explores the creation, expansion, and perpetuation of the material and imaginary spheres of spiritual domination and sanctity that surrounded Sufi saints and became central to religious authority, Islamic piety, and the belief in the miraculous. The cultural and social constructs of Islamic sainthood and the spatial inscription of saintly figures have fascinated and ignited scholars across a range of disciplines. By bringing together a broad scope of perspectives and case studies, this book offers the reader the first comprehensive, albeit variegated, exposition of the evolution of saintly spheres and the emplacements of spiritual power in the Muslim world across time and place. Contributors: Angela Andersen, Irit Back, Devin DeWeese, Daphna Ephrat, Jo-Ann Gross, Nathan Hofer, Ayfer Karakaya-Stump, Sara Kuehn, Bulle Tuil Leonetti, Silvia Montenegro, Alexandre Papas, Paulo G. Pinto, Fatima Quraishi, Eric Ross, Itzchak Weismann, Pnina Werber, and Ethel Sara Wolper"--